Drivers and Barriers of Corporate Social and Environmental Reporting (CSER) Practices in a Developing Country: Evidence from Bangladesh - Hossain, Mohammad; Rowe, Anna; Quaddus, Mohammed (IPA, 2012)
Purpose -The purpose of this paper is to provide insights into the drivers and barriers of corporate social and environmental responsibility (CSER) practices and reporting in Bangladesh by seeking the views of twenty senior managers of listed companies in Bangladesh. This paper explores the CSER phenomena in a developing country such as Bangladesh.Design/methodology and approach- This study is part of a larger project that followed a qualitative research approach. Semi-structured interviews were utilized to explore the perceptions of twenty senior managers in Bangladeshi listed companies. Observations along with local working experience also provided rich sources of information in this paper. Thus, understanding CSER practices and reporting phenomena, particularly drivers and barriers, constructivist ontology and interpretivist epistemology have been chosen.Findings- The findings of the study reveal that motivations for CSER mainly derived from management leadership, regulators, external stakeholder pressure, branding corporate image, poverty alleviation motive and social obligation motive. The barriers of CSER are attributable to lack of regulatory framework, tendency to non-compliance of the laws, socio economic problems, lack of awareness and education in sustainable development, and lack of initiatives from government. Whilst CSER practices and reporting in Bangladesh are in its infancy, senior managers are optimistic.Research implications- Most of the previous studies of CSER concentrated on the Western developed countries. This study takes on an engagement-based approach from an ‘emic’ perspective, which explores CSER phenomena in a developing country, particularly in Bangladesh. The findings are useful in informing the regulators, standard setters, stakeholders, as well as provide a benchmark for CSER managers and organizations in Bangladesh. The findings have also contributed significantly to the body of knowledge about CSER in developing countries.Limitations- Interviewees were selected on a voluntary basis. Due to the perceived sensitivity of social and environmental reporting issues, some respondents’ ‘politically correct’ responses may have prevailed either intentionally or unintentionally.Original Value-Most studies of CSER in Bangladesh mainly examined the volume of disclosure and are descriptive in nature using secondary data. However, this research followed the engagement based semi-structured in-depth interviews in seeking tacit knowledge from senior managers in order to understand the drivers and barriers of CSER in a rapidly emerging nation, such as Bangladesh.